Fonografski posnetki slovenskih ljudskih pesmi iz Bele krajine v SEM - Kunej, Drago (Etnolog. Nova vrsta (Ljubljana), 2009)
An article in the first volume of the scientific periodical Etnolog mentions that the Ethnographic Museum had "acquired" a phonograph and "collected" several tens of songs on cylinders. This may be understood in the sense that the Ethnographic Museum bought a phonograph and made field recordings with it. However, archive documents show that the museum''s staff never recorded anything with the phonograph. Nevertheless, the museum was in possession of wax cylinders with recorded folk songs from Bela krajina for some time, and these had been recorded by Juro Adlešič on the initiative of the OSNP in 1914. The article presents the circumstances of the origin of these records, how and when they were transferred to the museum, and to whom they were later passed on.
Keywords: Kunej, Drago, 1965-; slovenska ljudska glasba; slovenske ljudske pesmi; posnetki; terensko delo; fonografi; Bela krajina; White Carniola; zgodovinski pregledi; ethnology; etnologija; muzeji; Slovenski etnografski muzej (Ljubljana); muzejske zbirke